Correlation between Short-Term Memory and Achievement of Athletes - Ryandika Elvereza Mustari; Leonardo Lubis; Nani Kurniani (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Human activity is largely related to thought processing or cognition. One of the most important components of cognition is memory. Individuals who undergo heavy activities, such as athletes, use a lot of memory in the subject’s activities, especially during competitions. The purpose of this study was to find out whether there was a correlation between the capability of short term memory with the performance of an athlete during a competition, especially those measured by achievements.Methods: This study was an analytic observational correlation study with a cross-sectional design and involved 201 athletes as respondents from 12 branches of sports. The study was conducted in the Indonesian National Sports Committee (KONI) building from September to November 2015. Digit Span Forward and Backward were used to collect short term memory data and was performed after a consent form and the respondent’s identity was recorded. The athlete’s achievements data was gathered by an interview and recapitulation of athlete’s achievements in the last five years.Results: OA total of 186 data was analyzed and found a negative and insignificant correlation between achievement and short-term memory based on digit span tests both forward (r=0.095 p=0.196) and backward(r=0.039 p=0.196). Conclusions: There is no correlation between short term memory and the achievements of an athlete.